2016
DOI: 10.1002/hyp.10776
|View full text |Cite
|
Sign up to set email alerts
|

Estimating rainfall erosivity by aggregated drop size distributions

Abstract: Abstract:Rainfall erosivity is defined as the potential of the rain to cause erosion, and it can be represented by rainfall kinetic power. At first in this paper, the raindrop size distributions (DSD) measured by an optical disdrometer located at Palermo in the period June 2006-March 2014 and aggregated for intensity classes, are presented. Then an analysis of raindrop size characteristics is carried out, and the reliability of Ulbrich's distribution, using both the maximum likelihood and momentum estimate par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 28 publications
7
40
0
Order By: Relevance
“…In particular, they showed that the median volume diameter, D 0 , increases with rainfall intensity until I = 40 mm h −1 , and then it assumes a quasi‐constant value. A similar trend was observed by Carollo et al () in the scatterplot P n / I versus I : P n / I increases with I for I < 40 mm/h and assumes a quasi‐constant value for I ≥ 40 mm/h. This result confirms the approach of Wischmeier and Smith () even if a lower intensity threshold value than I t = 76 mm/h was identified.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, they showed that the median volume diameter, D 0 , increases with rainfall intensity until I = 40 mm h −1 , and then it assumes a quasi‐constant value. A similar trend was observed by Carollo et al () in the scatterplot P n / I versus I : P n / I increases with I for I < 40 mm/h and assumes a quasi‐constant value for I ≥ 40 mm/h. This result confirms the approach of Wischmeier and Smith () even if a lower intensity threshold value than I t = 76 mm/h was identified.…”
Section: Introductionsupporting
confidence: 87%
“…Carollo et al () demonstrated that the exponential distribution of Marshall and Palmer (), when it is referred to the unit area and time, can be assumed formally identical to a Gamma distribution (Ulbrich, ) with μ = 0.67 (Uijlenhoet & Stricker, ) and, as a consequence, from Equation it follows Pn=1069.527.2ρ[],12Λ4.67(),6+normalΛ4.67+normalΛ4.67(),12+normalΛ4.67I that provides the rainfall kinetic power when Λ parameter of Marshall and Palmer () distribution is known. Carollo et al (), using the following relationship (Uijlenhoet & Stricker, ; Ulbrich, ): D0=3.67+μΛ obtained the following estimate of Λ parameter by momentum method and μ = 0.67: normalΛ=4.34D0 in which D 0 is equal to the one deduced from the measured DSD.…”
Section: Introductionmentioning
confidence: 99%
“…Many other researches (Laws and Parsons, 1943;Atlas, 1953;Kelkar, 1959;Zanchi and Torri, 1980;Brandt, 1990;Jau-yau et al, 2008) propose a power law for describing the relationship D 0 -I implying that D 0 continues to increase indefinitely with I. This result is in contrast with other researchers which state that a maximum median volume diameter value is reached at high rainfall intensities (usually above 70-100 mm/h), after which the D 0 either stabilizes (Kinnell, 1981;Rosewell, 1986;Brown and Foster, 1987;Carollo et al, 2016a) or even decreases (Hudson, 1965;Baruah, 1973;Carter et al, 1974;Assouline and Mualem, 1989;Van Dijk et al, 2002).…”
Section: Is the Terminal Velocity Of The Drop Having Diameter D (Cm)mentioning
confidence: 87%
“…This choice allows to exclude both rainfall having a low erosive power and DSDs having a small sample size (Carollo and Ferro, 2015;Carollo et al, 2016a). This procedure provided 45802 DSDs for Palermo and 5537 DSDs for El Teularet with a sampling time of 1 min (named single DSDs) characterized by I, determined by Eq.…”
Section: Is the Terminal Velocity Of The Drop Having Diameter D (Cm)mentioning
confidence: 99%
See 1 more Smart Citation